A short G1 phase imposes constitutive replication stress and fork remodelling in mouse embryonic stem cells - Ahuja, Akshay K.; Jodkowska, Karolina; Teloni, Federico; Bizard, Anna H.; Zellweger, Ralph; Herrador, Raquel; Ortega, Sagrario; Hickson, Ian D.; Altmeyer, Matthias; Mendez, Juan; Lopes, Massimo (Nature communications, 2016)
Embryonic stem cells (ESCs) represent a transient biological state, where pluripotency is coupled with fast proliferation. ESCs display a constitutively active DNA damage response (DDR), but its molecular determinants have remained elusive. Here we show in cultured ESCs and mouse embryos that H2AX phosphorylation is dependent on Ataxia telangiectasia and Rad3 related (ATR) and is associated with chromatin loading of the ssDNA-binding proteins RPA and RAD51. Single-molecule analysis of replication intermediates reveals massive ssDNA gap accumulation, reduced fork speed and frequent fork reversal. All these marks of replication stress do not impair the mitotic process and are rapidly lost at differentiation onset. Delaying the G1/S transition in ESCs allows formation of 53BP1 nuclear bodies and suppresses ssDNA accumulation, fork slowing and reversal in the following S-phase. Genetic inactivation of fork slowing and reversal leads to chromosomal breakage in unperturbed ESCs. We propose that rapid cell cycle progression makes ESCs dependent on effective replication-coupled mechanisms to protect genome integrity. In fast proliferating embryonic stem cells (ESC) the DNA damage response is activated by mechanisms that are as yet elusive. Here, Ahuja et al. link the DNA damage response to replication stress in mouse ESCs, caused by a short G1 phase, and propose fork remodelling as maintaining genome stability in embryos.